Physiological changes during torpor favor association with Endozoicomonas endosymbionts in the urochordate Botrylloides leachii - Hyams, Yosef; Rubin-Blum, Maxim; Rosner, Amalia; Brodsky, Leonid; Rinkevich, Yuval; Rinkevich, Baruch (Frontiers in Microbiology, 2023)
Environmental perturbations evoke down-regulation of metabolism in some multicellular organisms, leading to dormancy, or torpor. Colonies of the urochordate Botrylloides leachi enter torpor in response to changes in seawater temperature and may survive for months as small vasculature remnants that possess torpor-specific, two new cell types, yet lack feeding and reproduction organs. Upon returning to milder conditions, the colonies rapidly restore their original morphology, cytology and functionality while harboring re-occurring microbiota, a phenomenon that has not been described in detail to date. Here we investigated the stability of B. leachi microbiome and its functionality in active and dormant colonies, using microscopy, qPCR, in situ hybridization, genomics and transcriptomics. A novel lineage of Endozoicomonas, proposed here as Candidatus Endozoicomonas endoleachi, was dominant in torpor animals (53-79% read abundance), and potentially occupied specific hemocytes found only in torpid animals. Functional analysis of the metagenome-assembled genome and genome-targeted transcriptomics revealed that Endozoicomonas can use various cellular substrates, like amino acids and sugars, potentially producing biotin and thiamine, but also expressing various features involved in autocatalytic symbiosis. Our study suggests that the microbiome can be linked to the metabolic and physiological states of the host, B. leachi, introducing a model organism for the study of symbioses during drastic physiological changes, such as torpor.